Performance Design Of Acid Gas Removalunit On Pertamina - Medco E&P Tomori Sulawesi – Indonesia - Kristinah Haryani (Jurusan Teknik Mesin - Politeknik Negeri Semarang, 2019)
Natural gas is a gaseous fossil fuel that contain primarily of main components, namely methane (CH4). Natural gas contains some impurities such as hydrogen sulfide (H2S), carbon dioxide (CO2), water vapor (H2O), and heavier hydrocarbons such as mercaptans or condensate (C5+).Acid gases need to be removed due to several factors, such as a healthy hazard, at the concentrations of 0.13 ppm H2S that can be perceived by smell, and to prevent corrosion problemsAcid gas removal unit (AGRU) is the process of removal acid gas (CO2 and H2S) to fulfill the specifications of the desired product gas sales. In Senoro CPP, the process used is amine treating by aMDEA absorbent material (activated Methyl Amine Diethanol).In order to simulate the process as accurate as possible, model phase selection DBR amine package was selected. Trial simulation is used to obtain the flow rate and purity of the product is optimal sweet gas. Variable experiments are feed gas temperatur inlet contactor (1), feed gas flowrate inlet contactor (2), temperature amine inlet contactor (3) and amine strength (4). According to the results of simulation, can be concluded as follows. There is no big different between design and simulation except CO2 in sweet gas. It is because of using MDEA while operating simulation and some parameters will be influence some result.